Phase I/II study on kilovoltage surface brachytherapy in conjunctival cancer: preliminary results - Sarria-Bardales, GR (2018)
Introduction: In ocular conjunctival carcinoma after surgery, adjuvant treatment has a role and kilovoltage surface brachytherapy opens a new door for the range of therapeutic options. Materials and methods: Between October 2014 and June 2017, at the National Institute of Neoplastic Diseases (INEN) from Peru, 39 patients with squamous cell carcinoma of ocular conjunctiva, T1-T3, resected, were selected to receive adjuvant treatment. The portable accelerator of 50-kV INTRABEAM (Carl Zeiss Meditec) was used, after local anaesthesia and blocking of ocular muscles movement. The doses used were 18 Gy for patients with free margins and 22 Gy for positive edges, according to calculation of equivalent dose of 2Gy per fraction of 46 and 66 Gy, respectively, assuming a tumoural α/β ratio of 8 Gy. The prescription was done to 2 mm depth. Results: The median age was 69 years, distributed evenly between both genders, with a median follow-up of 12 months. The surgical margins were 59% free and 41% committed, with no difference between the institutions where the surgery was performed (P = 0.069). The median tumour size was 7 mm with 2 mm of invasion, 61.5% was T2 and 35.9% T1. The mean time between surgery and irradiation was 1.5 months, 23.1% of patients developed grade I toxicity of spontaneous resolution, without evidence of greater degree in any case. The dose had no statistical relationship with toxicity (P = 0.533). One-year disease-free survival was 96.7%. Conclusions: Kilovoltage surface brachytherapy is an applicable and reproducible tool in the treatment of squamous cell carcinoma of ocular conjunctiva. The administered doses are well tolerated by patients with low levels of acute toxicity. Longer follow-up is needed to establish disease control rates and late toxicities.